Managing the urgent and unexpected : twelve project cases and a commentary - Wearne, S. H.; White-Hunt, Keith (Advances in project management., 2014)
This book explores what is different managerially if work is unexpected, its implementation is urgent and an immediate start is required. The authors draw on twelve cases ranging from the launch of the Freeview television system in the United Kingdom to the sifting and removal of the New York World Trade Center pile of debris following the 9/11 terrorist attack. They summarize how the response to each of these events was managed, demonstrate that opportunities may sometimes be created in the face of adversity and suggest how normal organizations can prepare to manage abnormal demands. And yet, organizations can, and should be prepared for the unexpected. The lessons offered here will help private and public organizations plan how to authorize and support future urgent work to take advantage of immediate new business opportunities or to protect or restore systems and services. --